2007
DOI: 10.1308/003588407x155464
|View full text |Cite
|
Sign up to set email alerts
|

Does the Referral and Selection for NHS-Funded Dental Implant Treatment in the UK Follow National Guidelines?

Abstract: INTRODUCTION The Royal College of Surgeons of England (RCSE) has provided a national guideline document detailing specific selection criteria for National Health Service (NHS) dental implant therapy in the UK. The aim of this study was to investigate whether these guidelines are being observed both in the referral and selection of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although the majority were in favour of implants the likelihood that this is provided on a private basis is high and there is as yet no NHS remuneration for implant therapy within the general dental services contract. 21,22 Specialist practitioners were least in favour (7%) of adhesive bridgework in comparison to all other groups (24%). This may be associated with concerns about the predictability of such bridgework especially when providing restorations in a private environment.…”
Section: Effect Of Location Of Practicementioning
confidence: 97%
“…Although the majority were in favour of implants the likelihood that this is provided on a private basis is high and there is as yet no NHS remuneration for implant therapy within the general dental services contract. 21,22 Specialist practitioners were least in favour (7%) of adhesive bridgework in comparison to all other groups (24%). This may be associated with concerns about the predictability of such bridgework especially when providing restorations in a private environment.…”
Section: Effect Of Location Of Practicementioning
confidence: 97%
“…As the purpose of implants in these cases, where normal oral anatomy has changed sometimes radically, is for the shown that there is a marked variation in the number of patients treated with dental implants within National Health Service hospitals but in most cases this follows the Royal College of Surgeons guidelines of 1997. 38,39 The increase in the spread of different types of implants in the present study refl ects the emergence of numerous companies developing and producing new implant systems since 1995. The most popular system used was Nobel Biocare (49%) followed by Straumann (26%).…”
Section: Discussionmentioning
confidence: 83%